Intra-osseous Jaw Lesions in Children and Adolescents: A 20-Year Retrospective Study in an Iranian Population - Taghavi, Nasim; Kooshki, Fahimeh; Shamloo, Nafiseh; Hosseini, Mohammadreza (Journal of Dental School, 2019)
Objectives The aim of the present study was to document the frequency and clinicopathologic features of intra-osseous jaw lesions in an Iranian pediatric population over a 20-year period. Methods Data were obtained from the archives of the Oral Pathology Department, Shahid Beheshti University of Medical Sciences, Tehran, Iran. The lesions were classified into four groups: (A) odontogenic cysts, (B) odontogenic tumors, (C) benign bone pathologies and (D) malignant bone tumors. The patients were divided into two age groups of (A) children (≤12 years old) and (B) adolescents (13 to 18 years old). Results Of 5,722 biopsy samples, 475 (58.2%) were diagnosed as intra-osseous lesions in patients aged 0-18 years with a male (55.2%) and mandibular (60.6%) predilection. The patients’ age ranged from 3 months to 18 years with a mean age of 12.5 years. Odontogenic cysts presented the most prevalent subgroup (51.3%) followed by benign bone pathologies (26.5%), odontogenic tumors (18.9%) and malignant bone tumors (3.1%). The most frequently observed lesions in descending order were dentigerous cyst (25.2%), radicular cyst (18.3%), central giant cell granuloma (14.9%), ameloblastoma (7.7%) and odontogenic keratocyst (5%). Conclusion Comparing our results with available data showed similarities in odontogenic cysts and benign bone pathologies. However, differences in odontogenic and malignant bone tumors were evident, which may be due to racial and geographical characteristics. Considering the limited data, further studies are recommended in this respect.